Irrational Choice of Bankers: Wealth or Welfare? - Aminullah Achmad Muttaqin; Iswan Noor; Silvi Asna Prestianawati (AIBPM Publisher, 2022)
The phenomenon of the high number of workers who are not absorbed in the workforce in Indonesia is a problem that is difficult to solve briefly. The lack of employment opportunities accompanied by problems with the level of education and expertise of the workforce in Indonesia has also become a polemic in the national development process. However, another fact occurs where workers tend to choose to leave several leading sectors in Indonesia, such as the financial sector, especially banking. It is feared that this condition will cause the banking sector as one of the sectors that drive the national economy, to lose qualified and loyal workers so that it will have an impact on production inefficiency in the banking sector and eventually will directly impact the community considering the function of the bank as an intermediary institution. This study aims to reveal the motives for changing workers' behaviour in banking by using qualitative methods and a phenomenological approach. This research is expected to contribute to the improvement of the employment system in the financial sector, especially banking, to absorb qualified and loyal workers to the company. Thus, macroeconomically, it is to reduce the voluntary unemployment rate in order to accelerate national development as a whole.